Analysis of Genetic Gain Tilapia Pandu F5 at Nursery I-III - Setiyono, Edi; Basuki, Fajar; Hastuti, Sri (Journal of Aquaculture Management and Technology, 2012)
The objectives of this research were to determine the genetic gain value of Tilapia Pandu F5 fry and to compare the growth between the fry of best 10 % (Top 10) of Tilapia Pandu F5and the average Tilapia Pandu F5 (without selection). This study was done at Satker PBIAT (Centre of Fresh Water Fish Culture Working Unit) Janti Klaten. The fries was kept in a happa (net cage) at the size of 4x2x1 m3 from nursery I-III. The stocking density was 500 fries/cage. The results of this investigation shows that the weight genetic gain of Tilapian Pandu F5 at nursery I-III was at the range of 60,12 % - 88,58 %. It was also shown that the best 10 % selection (Top 10) Tilapia Pandu F5 fries growth better than the average Tilapia Pandu F5 fries without selection.